Meeting the ethical challenges of leadership : casting light or shadow - Johnson, Craig E. (Craig Edward), 1952- (Thousand Oaks, California : SAGE, 2025)
'Ethics is at the heart of leadership. Leaders must make every effort to make ethical decisions and foster ethical behavior among followers. The Eighth Edition of Meeting the Ethical Challenges of Leadership: Casting Light or Shadow explores the ethical demands of leadership and the dark side of leadership. Bestselling author Craig E. Johnson takes an interdisciplinary approach, drawing from many fields of research to help readers make ethical decisions, lead with integrity, and create an ethical culture. Packed with dozens of real-world case studies, examples, self-assessments, and applications, this fully-updated new edition is designed to increase students' ethical competence and leadership abilities.'--Publisher's website.
The leader's light or shadow -- Stepping in and out of the shadows -- The leader's character -- Combating evil -- Ethical perspectives -- Ethical decision making and behavior -- Exercising ethical influence -- Normative leadership theories -- Building an ethical small group -- Creating an ethical, inclusive organizational climate -- Meeting the ethical challenges of leadership in a global society -- Ethical crisis leadership.
Includes bibliographical references (pages 479-536) and index.
Buku bacaan asas prasiswazah 2023/24 Fakulti Ekonomi Pengurusan.
Keywords: Leadership -- Moral and ethical aspects; Leadership -- Aspect moral